2019
DOI: 10.1186/s12913-019-4754-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of drug information leaflets for non-steroidal anti-inflammatory drugs in Palestine: local versus imported products

Abstract: BackgroundDrug information leaflets (DILs) are written for patients and health care providers to show how to use the medications safely and effectively, in order to reach the required therapeutics outcomes. This comparative study was conducted to evaluate various DILs of non-steroidal anti-inflammatory drugs (NSAIDs) that are produced in Palestine, along with their imported equivalents.MethodsThirty-five DILs of NSAIDs were analyzed and evaluated in a cross-sectional comparative study. Thirty-one statements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…The median word count [Q1–Q3] was 52.0 [42.0–71.3] and 160.0 [130.0–260.0] for the local and imported leaflets, respectively. Similar results were also found in many other Palestinian studies (Arandy et al, 2019; Eshtayeh et al, 2019; Qatmosh et al, 2017; A. Sawalha et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The median word count [Q1–Q3] was 52.0 [42.0–71.3] and 160.0 [130.0–260.0] for the local and imported leaflets, respectively. Similar results were also found in many other Palestinian studies (Arandy et al, 2019; Eshtayeh et al, 2019; Qatmosh et al, 2017; A. Sawalha et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of the information content of the DLs was carried out in many previous studies (Al-Aqeel, 2012;Arandy et al, 2019;Chhaya, 2017;Eshtayeh et al, 2019;Khamas et al, 2019;Qatmosh et al, 2017;Rahim & Rafiq, 2013;Shivkar, 2009). Some of these depended on the presence of particular topics in the PIs (Al-Aqeel, 2012;Chhaya, 2017;Khamas et al, 2019;Rahim & Rafiq, 2013;Shivkar, 2009), while other studies built their assessment on both the presence of certain headings and the amount of information provided in the PIs (Arandy et al, 2019;Eshtayeh et al, 2019;Qatmosh et al, 2017;. In Palestine, many studies were conducted using similar principles to assess the quality and quantity of information provided in the PIs (Arandy et al, 2019;Eshtayeh et al, 2019;Qatmosh et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Palestine, surveys involving 594 consumers found that 45–52% always read PIs [ 115 , 116 ]; one also noted that most consumers wanted information in Arabic [ 116 ] and that written information was sometimes vague or not useful. A study focusing on administration of oral drops noted inaccurate instructions [ 118 ], while four further studies assessed the content of PIs [ 117 , 119 121 ], consistently finding both incomplete information and PIs for locally manufactured products having greater deficiencies in content than those for imported products. Such differences were also reported regarding PIs available in Abu Dhabi [ 134 ], which concurs with findings from other countries [ 75 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, patients will not know the divisibility of the tablet unless they ask health professionals more regarding that topic. 8 In Malaysia, there is no tablet-splitting guideline implemented by the government for health professionals. Under this circumstance, little is known about the tablet splitting practice in Malaysia.…”
Section: Knowledge Attitudes and Practices Of Pills Splitting In Malaysiamentioning
confidence: 99%